Relaciones filogenéticas entre tipos de cacao (theobroma cacao l.): forastero, trinitario y nacional, basadas en marcadores morfológicos y secuencias nucleotídicas de la región ITS; y su posible uso en la identificación de clones. - Zambrano Cruz, Jonathan Carlos (2017)
The present research project was carried out in the Biotechnology Laboratory of the State Technical University of Quevedo and in the Farms; Experimental "La Represa" owned by the State Technical University of Quevedo, located at Kilometer 7.5 of Vía Quevedo-San Carlos; in the Faita precinct, Province of Los Ríos, and Finca "Maquita" owned by the Maquita Fundación Comercializando Hermanos (MCCH), located in Cantón Buena Fe, 5 km via Santo Domingo, Limones Campus - Los Ríos Province. The general objective was to determine the phylogenetic relationships between types of cocoa, Forastero, Trinitario and Nacional, based on morphological markers and nucleotide sequences of the ITS region "and to establish the cocoa group to which a clone with desirable characteristics belongs to the Pincay clone. For which quantitative and qualitative morphological variables of the leaf, flower, fruit and seed were taken and for the molecular analysis of the ITS region leaf samples of 10 plants of each clone were taken for DNA extraction and amplification by specific primers in (PCR) A large genetic diversity and variations in the characters within the same clone were determined by the morphological analysis, whether due to environmental, phenological or cross-fertilization products. The molecular study of the ITS region with specific primers, did not identify polymorphic regions that allow identifying each of the groups of cocoa under study, because the types of cocoa analyzed, share 100% similarity in this region. The Pincay clone shares diverse morphological characteristics that resemble the National and Forastero cacaos. These phenotypic characteristics do not have significant differences existing the possibility of being a hybrid related to certain groups of the region.